Assistive Social Robots for People with Special needs - Nadia Magnenat-Thalmann; Zhijun Zhang (IAES Indonesia Section, 2014)
An increasing number of elderly people leads todemand for social robots to support health care and independentlife. An overview of various potential applications of social robotsis provided in this paper. In addition, the latest research progressin our institute is presented, i.e., multi-party interaction, gesturerecognition, affective computing, and attention capture. All theresearch and applications demonstrate that social robots are goodassistive robots for people with special needs.